Analysis of the Noise Level at the Muhammadiyah KH. Ahmad Dahlan S. Parman Complex, Banjarmasin - Hardiani, Dyah Pradhitya; Ruhaidani, Emma (Universitas Muhammadiyah Yogyakarta, 2023)
The traffic density in Banjarmasin will have an impact on the environment such as the noise which causes health problems to humans. The noise in the school area, it will damage for concentration of students, teaching and learning activities inefficient. The purpose of this study was to determine the noise level in the College Complex of Muhammadiyah K.H Ahmad Dahlan, Banjarmasin. Measurement is carried out at 4 points and used Sound Level Meter (SLM). Noise data processing is calculated by the equivalent noise level (Leq). The results show that noise value exceeded the noise quality standard according to the Environmental Decree 1996 for noise levels in schools. The highest noise value reached 80.29 decibels while the lowest value was 63.04 decibels. Based on the results, it is necessary to reduce noise levels in this school area, so that teaching and learning activities can run properly.